Reshaping Tomorrow : Is South Asia Ready for the Big Leap? - Ghani, Ejaz (New Delhi: Oxford University Press, 2013)
What will South Asia look like in 2025? The optimistic outlook is that India, which accounts for 80 per cent of the regional economic output, is headed towards double-digit growth rates. South Asia too will grow rapidly, primarily due to India. The pessimistic outlook is that, given huge transformational challenges facing the region, growth should not be taken for granted. Which of these two outlooks is likely to prevail? This is what this book is all about. It is about the future, and not the past, and how to make smart choices about the future. There is strong empirical justification in favor of the optimistic outlook. Growth will be propelled higher by young demographics, improved governance, rising middle class, and the next wave of globalization. There is democracy, for the first time since independence, in all countries in the region. Young demographics will result in nearly 20 million more people joining the labour force, every year, for the next two decades. Almost a billion people will join the ranks of the middle class. India's middle class is well-educated, enterprising, innovative, and more demanding of better services, products, and governance. The region will benefit from the new wave of globalization in services, and increased international migration and human mobility. Indeed the drivers of growth seem to have already moved from the rich world to the poor world. The room for catch-up is huge, given the big gap in average income between South Asia and the rich countries.